Cytokines and Their Genetic Polymorphisms Related to Periodontal Disease - Kozak, Małgorzata (J Clin Med, 2020)
Periodontal disease (PD) is a chronic inflammatory disease caused by the accumulation of bacterial plaque biofilm on the teeth and the host immune responses. PD pathogenesis is complex and includes genetic, environmental, and autoimmune factors. Numerous studies have suggested that the connection of genetic and environmental factors induces the disease process leading to a response by both T cells and B cells and the increased synthesis of pro-inflammatory mediators such as cytokines. Many studies have shown that pro-inflammatory cytokines play a significant role in the pathogenesis of PD. The studies have also indicated that single nucleotide polymorphisms (SNPs) in cytokine genes may be associated with risk and severity of PD. In this narrative review, we discuss the role of selected cytokines and their gene polymorphisms in the pathogenesis of periodontal disease.